Mental health in the kingdom of God - Cook, Christopher C. H. 1945- (2020)
Mental disorders are both common and disabling worldwide. They affect beliefs, emotions, identity and relationships in such a way as to impact upon the very essence of human experience. They are associated with stigma and prejudice, and they disproportionately affect those who are poor and those who belong to marginalized groups within society. Increasing attention has been given in recent years to the importance of spirituality for mental health, but in research it is impossible to distinguish between spirituality and the psychological variables that it purports to influence. Those things that are identified as being the concerns of mental health professionals overlap significantly with the concerns of religion. This overlap is examined here in relationship to the Synoptic Gospel accounts of the mission, ministry and teaching of Jesus. It is proposed that Jesus' teaching on the kingdom of God was centrally concerned with things that we now consider to be the domain of mental health. For Christians, mental health may be understood as the ability to fulfil vocation within the kingdom of God. A more critical theological understanding of mental health is needed to better inform the mission of the Church of England.
Keywords: Kingdom of God; Mental Health; Mission; Spirituality; Vocation